Analysis of characteristics and influencing factors of agricultural carbon emission in Jiangxi Province, southeast China - Fu, Shuai; Feng, Yingxiang; Yu, Jie; Liu, Yaobin; Xu, Bingxian; Xu, Bingxian; Xu, Bingxian; Liu, Shenyi; Liu, Shenyi; Liu, Linyang; et al. (International Journal of Agricultural and Biological Engineering, 2025)
With the continuous economic development and population growth, carbon emissions from farmland utilization cannot be underestimated. In this study, the life cycle assessment method was employed to determine the accounting boundaries and sources of carbon emissions from cultivated land use. A STIRPAT model and a carbon emissions accounting system from cultivated land utilization were developed to explore the characteristics and influencing factors of carbon emissions in Jiangxi Province. Additionally, targeted countermeasures were proposed to promote low-carbon utilization of cultivated land in the region. The results show that the total carbon emission underwent four distinct stages: “steady growth, fluctuating growth, rapid decline, and leveling off”. Specifically, carbon emissions decreased from 220.2 t in 1990 to 17.8 t in 2019. In terms of carbon emission intensity, the overall trend is downward, with the intensity dropping below 7 t/hm2 after 2009. The number of agricultural population, total agricultural machinery power, and rural investment were identified as significant driving factors for carbon emissions from cultivated land utilization in Jiangxi Province. Conversely, land productivity and investment in science and technology exhibited inhibitory effects on carbon emission growth. Enhancing technological investment and improving land productivity were found to be conducive to promoting low-carbon utilization of cultivated land in Jiangxi. Key words: cultivated land utilization; STIRPAT model; carbon emission accounting; driving factors DOI: 10.25165/j.ijabe.20251806.9453 Citation: Fu S, Feng Y X, Yu J, Liu Y B, Xu B X, Liu S Y, et al. Analysis of characteristics and influencing factors of agricultural carbon emission in Jiangxi Province, southeast China. Int J Agric & Biol Eng, 2025; 18(6): 168–174.